The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1365-2826.1990.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrial Natriuretic Peptide on the Vasopressin Response to Osmotic and Hemorrhagic Stimuli in Dogs

Abstract: Effect of atrial natriuretic peptide (ANP) on the vasopressin response to osmotic stimulation (Experiment I) as well as to hemorrhage (Experiment II) was investigated in anesthetized dogs. Moreover, cardiovascular function and renal water and electrolyte excretion were studied. In Experiment I , 2.5 M NaCI, containing 0.02 pg.kg ' of ANP, was infused intravenously at a rate of 0.2 ml.kg-'. min ' after one bolus injection of 0.75 pg.kg ' ANP (HSA group). In the control group, 2.5 M NaCl alone (HS group) was inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Moreover, there are interactions between AVP and ANH release: AVP enhances ANH release, while ANH attenuates AVP release (10,11). However, the release of AVP and ANH and their interaction in renal water and electrolyte metabolism during the condition of chronic mineralocorticoid excess remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are interactions between AVP and ANH release: AVP enhances ANH release, while ANH attenuates AVP release (10,11). However, the release of AVP and ANH and their interaction in renal water and electrolyte metabolism during the condition of chronic mineralocorticoid excess remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that increased plasma ANH may take part in the suppression of AVP release in response to changes in plasma osmolality within the physiological range because increased blood pressure, which activates the baroreceptor reflex leading to the attenuation of AVP release, was not observed in dextran hypertonic saline administration. Moreover, Inoue et al (20) from our laboratory reported that increases in plasma ANH, produced by exogenous administration of ANH, of more than 233 pmol/1 attenuated the AVP response to hypertonic saline in dogs. In fact, in the present study, real increases in plasma ANH in the 9% dextranhypertonic saline group are in almost the same range as previously reported values (233 pmol/1).…”
Section: Discussionmentioning
confidence: 77%